Neural networks - Dhaliwal, Ranjodh Singh; Lepage-Richer, Théo; Suchman, Lucy 1951- (University of Minnesota Press, 2024)
"Far from signaling the ultimate convergence of human and machine intelligence, neural networks highlight the technologization of neurophysiology that characterizes virtually all strands of neuroscientific and AI research of the past century. Taking this traffic as its starting point, Neural Networks explores how cognition came to be constructed as essentially computational in nature and how countermovements provide resources for thinking otherwise"--
Keywords: Künstliche Intelligenz; Neurophysiologie; Wissenschaft; Neural networks (Neurobiology); Neural networks (Computer science)